From the relationship between economics and physics to econophysics - Eser, Rüya; Kırer, Hale (BILGESEL YAYINCILIK SAN & TIC LTD, KUSKONDU SOKAK KILIM APT 14-8, A AYRANCI, ANKARA, 06550, TURKEY, 2009)
From the relationship between economics and physics to econophysics This paper is intended to review the literature investigating the interaction between physics and economics, The relationship between these two disciplines has been a repeated topic in the history of science, and recently the interaction between the two fields has been renewed by several new findings of physicists working on problems in social science. Econophysics, known as an interdisciplinary field of research, was born in 1995 and has grown extensively over the last decade. In this paper, after providing a definition and a brief historical background of econophysics, a summary of some applications of models and methods of statistical physics to economic problems are introduced Furthermore the study, based on a survey of the relevant literature, maintains that the methodology of econophysics has its own weaknesses.
Keywords: econophysics; statistical physics; scaling law; power law; entropy; worrying trends; ekonofizik; istatistiksel fizik; ölçekleme kanunu; güç yasası; entropi; endişe verici eğilimler